Implementation of Collaborative Learning during the Applied Pharmaceutical Calculations Laboratory at the School of Pharmacy from the Universidad de Costa Rica - Juan José Mora Román (Revista Electrónica Educare)
The School of Pharmacy is currently facing a problem due to little or no communication among students of the same class or same academic level. Collaborative learning is a methodological strategy that goes beyond just working in groups. Small groups are formed and, after receiving instructions from the professor, group members exchange knowledge and work on an assignment until every person in the group has understood and completed the task, thus learning through collaboration. The main elements of this learning technique include: intentional design through the use of activities prepared by the teacher, collaboration through the active commitment of all the members of the work team, and significant learning through the increase of individual and collective in-depth knowledge on a given topic. Due to the foregoing, this learning experience was conducted during three sessions of the Applied Pharmaceutical Calculations Laboratory (FA-2023) during the second semester of 2012.  During these sessions, students were paired and assigned specific tasks that had to be completed before, during and after each lab session. In order to determine the result of the strategy used, the grades obtained by all the groups (24 students) in quizzes and reports during those sessions were compared against the grades obtained in both items during the sessions where no collaborative learning approach was used. In addition, a survey in the form of a questionnaire was used to know the students’ opinion regarding this methodological strategy. Data was examined using a sociodemographic analysis for age and gender, and a descriptive analysis with frequency distribution for the rest of the items in the questionnaire. Results obtained show an enriching experience from the perspective of both the professor and the students. Consequently, the implementation of this strategy is necessary and advisable for the education processes of all learning levels in Costa Rica.